Characterization of N4-like Pseudomonas phage vB_Pae-PA152 isolated in Thailand - Srichaisupakit, Akkaraphol (Agriculture and Natural Resources, 2022)
Bacteriophage, a natural predator of bacteria, is an abundant microorganism existing in ecological habitats. Bacteriophages are being isolated and characterized for biotechnological and medical applications. In this work, phage vB_Pae-PA152 was enriched from drain water and propagated using Pseudomonas aeruginosa ATCC 27853 as a host, since it only infects P. aeruginosa. Phylogenetic analysis revealed that vB_Pae-PA152 was an N4-like virus, belonging to the same clade with the Luzseptimaviruses, Pseudomonas phages KPP21, LUZ7 and vB_Pae_AM.P2. The burst size of vB_Pae-PA152 was 60 plaque-forming units/infected cell. Furthermore, in vitro assays showed that the phage could control planktonic P. aeruginosa cells for up to 48 hr, including the ability to disrupt P. aeruginosa biofilm. The lytic N4-like bacteriophage vB_Pae-PA152 infecting P. aeruginosa was isolated and characterized, which might be useful in future applications.